Zoom and Padlet: A Solution for Teaching Listening Online - Thinh Tien Vu; Huyen Diem Bich Bui (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
How to teach listening skills effectively has always been a concern, especially when it is conducted online during the time of the COVID-19 pandemic. This research aims to examine the impact of using Zoom and Padlet in teaching Listening online for B2 students at a university in Vietnam. The participants included 76 students, separated into a control group and an experimental group with pre-test mean scores of 57.50 (SD=7.24) and 57.39 (SD=6.27), respectively. The treatment applied to the experimental group was a combination of Zoom’s main room, breakout rooms, and Padlet interactive tool. After fifteen weeks, both groups were required to do a post-test, and then the experimental participants were asked to fill in a survey. Findings from post-tests revealed that both groups got improved, but more improvement was found in the experimental group. The survey results reported a high level of students’ concentration and enjoyment of learning when the applications of Zoom and Padlet were combined. In light of the outcomes, further research on a larger scale should be carried out to provide ESL listening teachers with an alternative in teaching their listening lessons online effectively